The Position of Clinical Pharmacists in Delivering Advanced Pharmacy Practice Education and Services - Woldu, Minyahil Alebachew; Berha, Alemseged Beyene; Haile, Demisew Berihun; Tadesse, amrat Assefa; Worku, Belete Ayalneh; Senbeta, Mamo Fayissa; Tamiru, Melaku Tileku (Indian Journal of Pharmacy Practice)
The pharmacist’s role in health systems continues to evolve from a product focus to a patient-centered care model ensuring the safe and effective use of medications in all practice settings. The scope of pharmacy practice now includes patient-centred care with all the cognitive functions of counselling, providing drug information and monitoring drug therapy, as well as technical aspects of pharmaceutical services, including medicines supply management. Clinical Pharmacy consist of all the services accomplished by pharmacists practicing in hospitals, community pharmacies, nursing homes, home-based care services, clinics and any other setting wherever medicines are prescribed and used. Advanced pharmacy practice should be handled and delivered by facilities where high standards of pharmaceutical care and instruction are available and preceptors and educators should be actively engaged in the delivery of high-quality pharmaceutical care, and spend a majority of their time providing pharmaceutical care in their facility.
Keywords: Pharmacy Practice; Clinical pharmacy; Advanced Pharmacy Practice